Enhancing Student Comfort in Lampung Islamic Boarding Schools: Communication and Psychological Support - Muhajir, Muhajir; Kholis, Nur; Syahid, Akhmad (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
Islamic boarding schools (pesantren) are renowned for providing quality education and fostering character development, but they also face challenges in ensuring student well-being. This study explores how Lampung pesantren address student discomfort, a barrier to both academic and personal growth. Using in-depth interviews with administrators, supervisors, and psychologists from three institutions (Sabilil Muttaqin Tanggamus, Mathla'ul Anwar Lampung Selatan, and Al-Amin Central Lampung), this qualitative field research investigates efforts to improve student comfort. The research identifies two key strategies employed by the boarding schools to improve student comfort. Firstly, extensive verbal communication is prioritized. Mudabbirs provide daily support and guidance to students, fostering a sense of trust and openness in communication. Secondly, the schools actively engage with parents and guardians through regular monthly meetings, ensuring a collaborative approach to student development that encompasses both academic and non-academic aspects. Notably, the involvement of external psychologists is emerging as a successful practice. Psychologists conduct student assessments, enabling data-driven guidance tailored to individual needs. This addresses not only behavioral issues but also underlying psychological factors. This study sheds light on the proactive measures taken by Lampung Islamic boarding schools to prioritize student comfort. The findings highlight the importance of effective communication, parental involvement, and professional psychological support in fostering a positive and nurturing learning environment for students.